Soroprevalência do vírus da Hepatite B (HVB) no município de Macapá, Amapá, Brasil - (:unkn) unknown (UNIFAP - Universidade Federal do Amapá)
Introduction: Viral hepatitis are diseases triggered by viruses with tropism by hepatocytes, presenting similar signs and symptoms, but with differences related to possible means of contamination and degree of infection. It is currently considered a serious public health problem due to the associated morbidity, with evolution to hetocellular carcinoma, which is the ninth leading cause of death on the world stage.Objective: The objective was to determine the prevalence and to establish the epidemiological profile of viral hepatitis B in the municipalities of Macapá, State of Amapá. Methodology: This is a qualitative-quantitative study. All participants in this study answered a standardized questionnaire containing questions related to personal identification, family composition and habits and practices that may be related to the risk of infection by hepatitis B virus and submitted to rapid test for HBV and determination of antibodies against the virus surface antigen of hepatitis B virus. Results and discussions: We identified the main risk foams that the study is exposed to, as a means of contamination, familar conviviality (sharing of personal objects) and sexual counts unprotected. In the rapid tests, no sample was reactive for the presence of the virus. In the assay for antibody determination 65.17% of the samples were positive for the presence of antibodies, from 12.36% presented concentration below 20 mIU/mL, confirming, according to clinical practice the presence of the antibody, but not necessarily immunity. Conclusions: These results serve as a basis to assist in the elaboration of campaigns or strategies for prevention and control of these infections that are more adequate for each regional health and in the basic planning strategies of the STD/AIDS state program and HEPATITES VIRES
Keywords: Hepatite por vírus - Tratamento - Macapá (AP); Hepatite por vírus - Diagnóstico - Macapá (AP); Soroprevalência; Macapá (AP); Doença hepática; Doenças transmissíveis; CNPQ::CIENCIAS DA SAUDE::SAUDE COLETIVA::SAUDE PUBLICA; CNPQ::CIENCIAS DA SAUDE::MEDICINA::CLINICA MEDICA::DOENCAS INFECCIOSAS E PARASITARIAS; VALIDAÇÃO QUÍMICA-BIOLÓGICA DE FÁRMACOS DE ORIGEM SINTÉTICA E NATURAL; BIOLOGIA FARMACÊUTICA